ANALISIS SANITASI LINGKUNGAN DAN KEBERADAAN VEKTOR TIKUS DI PANTI ASUHAN AL-ISTIKLAL - Rasyid , Zulmeliza; Puspita Sari, Nila; Hayana; Lusiana, Novita; Sohor, Suherman (Institut Kesehatan dan Teknologi Al Insyirah, 2024)
Environmental sanitation is an effort to monitor and control environmental elements such as clean water and waste, personal hygiene in public places, clean and healthy food processing, and the absence of hazardous substances in the air. This research aims to identify and analyze environmental conditions and the presence of rat vectors at the Al-Istiklal Orphanage, Pekanbaru City. This research uses an observation approach and in-depth interviews to examine current conditions. Five informants were research subjects. The research results show that the sanitary conditions at the Al-Istiklal orphanage are still poor, as shown by SPAL: many piles of rubbish smell bad and do not have lids; rubbish at the orphanage is not sorted before being thrown away and burned; some rooms in the orphanage were not sorted before being burned; and Some rooms have an outdoor and adjoining kitchen, and the windows do not open. Several mice were found in the orphanage. Orphanages must pay more attention to environmental sanitation issues, such as SPAL, food processing, waste processing, and residential density, as well as the presence of rat vectors.